Ivan Mykolaiovych Vyshnevskyi (26.05.1938 - 06.08.2017) - Institute for Nuclear Research (Ядерна фізика та енергетика)
Brief biography and scientific achievements of Ivan Mykolaiovych Vyshnevskyi in connection with his death.